Otherness and National Identity in 19th-Century Spanish Literature - Cantos Casenave, Marieta; Muñoz Sempere, Daniel (Brill, 2022)
Which were the mechanisms by which certain groups were positioned at the margins of national narratives during the nineteenth century, either via their exclusion from these narratives of through their incorporation into them as 'others'? By engaging with shifting ideas of exclusion and difference, the authors in this book reflect upon the paradoxical centrality of the subaltern at a time when literature was deployed as a tool for nation building. The lasting presence of the Jewish and Moorish legacy, the portrayal of gypsy characters, or the changing notions of femininity in public discourse exemplify the ways in which images of marginal 'types' played a central role in the configuration of the very idea of Spanishness. ¿Cuáles fueron los mecanismos mediante los que ciertos grupos fueron relegados a los márgenes del relato nacional durante el siglo XIX, bien a través de su exclusión de dichos relatos, bien a través de su incorporación a ellos como "otros"? A través del análisis de las ideas de exclusión y diferencia, los autores de este libro reflexionan sobre la paradójica centralidad de lo marginal en una época en la que la literatura fue una herramienta fundamental para la construcción de la nación. La pervivencia del legado judío y morisco, la representación de personajes gitanos o las distintas nociones de feminidad presentes en el discurso público ejemplifican las formas en que las imágenes de "tipos" marginales desempeñaron un papel central en la configuración de la idea de españolidad.